Spinal tuberculosis in children. Issue 8 (25th June 2012) - Eisen, Sarah; Honywood, Laura; Shingadia, Delane; Novelli, Vas
Abstract : Objectives: To review our experience of spinal tuberculosis (TB) at a major UK paediatric tertiary referral centre. Methods: The authors performed a retrospective case survey of 21 patients admitted to Great Ormond Street Hospital over a 15-year period (1995–2010) with confirmed or presumed spinal TB. Data were collected concerning demographics, clinical, laboratory and radiological characteristics, treatment and clinical outcome. Results: Only one patient was of Caucasian origin. Four (19%) had a previous diagnosis of TB, 11 (52%) a known contact, 10 (48%) had received BCG vaccine and none were HIV-positive. Clinical presentations included systemic symptoms (18 patients), back pain (16 patients), deformity (five patients) and neurological deficits (12 patients). Mycobacterium tuberculosis was isolated from 14 patients (67%) including one multi-drug resistant strain. Spinal cord compression or critical stenosis was demonstrated in eight patients (38%). All received TB treatment for at least 12 months; six patients received treatment for a longer period. Seven (33%) underwent surgical intervention. Seventy-five per cent showed clinical and radiological resolution after treatment. No patients died or suffered long-term neurological deficit. Conclusions: Spinal TB in children needs a high index of suspicion for diagnosis. Early referral to an expert centre allows a multidisciplinary approach to management. The authors recommend that treatment should be individually tailored and may need to exceed 12 months in cases of poor adherence, extensive disease or drug resistance.